In Career Counselling, Work Life Dispositions of Young People Are Key to Understanding Their Career Paths - Longo, María Eugenia; Bourdon, Sylvain; Dionne, Patricia (Canadian Journal of Counselling and Psychotherapy, 2019)
Labour market complexity and flexibility along with lifelong learning demands are resulting in greater diversity in career paths and ongoing demand for individuals to adapt. These changes call for new perspectives in career counselling research and intervention. This article analyzes data from a qualitative longitudinal study of the education and occupation paths of young postsecondary students, showing that "work life dispositions" of Cegep students in Quebec are key to understanding their careers.